Real-time Ball Detection and Tracking using Raspberry PI - Aryani, Dharma; Dewi, Kartika; Ta.by, Fery; Sanggaria, Evita Putri (Politeknik Negeri Ujung Pandang, 2023)
This paper presents a real-time system for ball detection and tracking system which is reliable in any conditions. Images from the webcam are processed by openCV library running on a Raspberry Pi to move the camera pan and tilt servo and two DC motors to drive the robot body using the Arduino Nano microcontroller. Â The webcam is integrated in a robot prototype to represent the wheel football robot type. The results show that a ball tracking webcam system is obtained with the capability to detect a ball with a diameter of 17cm within a maximum distance of 200 cm, a stable ball reading when the light intensity is at 32 lux and above. Furthermore, the experimental results demonstrated the systemâ€™s robustness in detecting and tracking ball in different distance and ligthing conditions.